2009
DOI: 10.1007/s11665-009-9536-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of AA5083 Material-Microstructure Evolution During Butt Friction-Stir Welding

Abstract: A concise yet a fairly comprehensive overview of the friction stir welding (FSW) process is provided. This is followed by a computational investigation in which FSW behavior of a prototypical solution-strengthened and strain-hardened aluminum alloy, AA5083-H131, is modeled using a fully coupled thermo-mechanical finite-element procedure developed in our prior study. Particular attention is given to proper modeling of the welding work-piece material behavior during the FSW process. Specifically, competition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 35 publications
(19 reference statements)
2
66
0
1
Order By: Relevance
“…So Pe will be equal to 561 which indicates that material flow plays a major role in heat transfer during the FSW process of steel especially under the tool shoulder. The importance of material flow in heat transfer during the FSW process was also reported in [14] for modelling aluminium AA5083-H131 and they found that Pe number was still high even when the thermal conductivity is very high.…”
Section: W5 W6mentioning
confidence: 59%
See 1 more Smart Citation
“…So Pe will be equal to 561 which indicates that material flow plays a major role in heat transfer during the FSW process of steel especially under the tool shoulder. The importance of material flow in heat transfer during the FSW process was also reported in [14] for modelling aluminium AA5083-H131 and they found that Pe number was still high even when the thermal conductivity is very high.…”
Section: W5 W6mentioning
confidence: 59%
“…This is because the heat affected region in FSW is very small compared to the whole length of the workpiece [3,[12][13][14]. The tool and the plate were considered in the fully sticking condition.…”
Section: The Geometry Used To Model the Tooling And Workpiecementioning
confidence: 99%
“…The welding process begins when the frictional heat developed between the shoulder and the surface of the welded material softens the material, resulting in severe plastic deformation. The material is transported from the front of the tool to the trailing edge, where it is forged into a joint (Grujicic et al 2010;Nandan et al 2008). Consequently, the friction-stir welding process is both a deformation and a thermal process occurring in a solid state; it utilises the frictional heat and the deformation heat source to bond the metal under the applied normal force.…”
Section: Process Principlesmentioning
confidence: 99%
“…Thus, under the correct conditions of heat and flow material in the front moves from the advancing side (AS) to the retreating side (RS) and consolidates at the back to form a sound joint. The material from the leading edge is exported towards the trailing edge where it is forged into a joint [11]. Roughly, with every complete rotation of the tool, a sufficient amount of energy builds up to squeeze out semi-circular shells from the base material.…”
Section: Introductionmentioning
confidence: 99%